Charybdotoxin unbinding from the mKv1.3 potassium channel: a combined computational and experimental study - Khabiri, Morteza; Nikouee, Azadeh; Cwiklik, Lukasz; Grissmer, Stephan; Ettrich, Rüdiger (The journal of physical chemistry. B, 2011)
Charybdotoxin, belonging to the group of so-called scorpion toxins, is a short peptide able to block many voltage-gated potassium channels, such as mKv1.3, with high affinity. We use a reliable homology model based on the high-resolution crystal structure of the 94% sequence identical homologue Kv1.2 for charybdotoxin docking followed by molecular dynamics simulations to investigate the mechanism and energetics of unbinding, tracing the behavior of the channel protein and charybdotoxin during umbrella-sampling simulations as charybdotoxin is moved away from the binding site. The potential of mean force is constructed from the umbrella sampling simulations and combined with K(d) and free energy values gained experimentally using the patch-clamp technique to study the free energy of binding at different ion concentrations and the mechanism of the charybdotoxin-mKv1.3 binding process. A possible charybdotoxin binding mechanism is deduced that includes an initial hydrophobic contact followed by stepwise electrostatic interactions and finally optimization of hydrogen bonds and salt bridges.
Keywords: Molecular Dynamics Simulation; Charybdotoxin; Protein Structure, Tertiary; vazebná místa; statická elektřina; sekvence aminokyselin; vazba proteinů; terciární struktura proteinů; Molecular Sequence Data; simulace molekulární dynamiky; charybdotoxin; draslíkový kanál Kv1.3; Amino Acid Sequence; molekulární sekvence - údaje; Sequence Alignment; Patch-Clamp Techniques; Thermodynamics; metoda terčíkového zámku; Kv1.3 Potassium Channel; termodynamika; Protein Binding; Static Electricity; sekvenční seřazení; hydrofobní a hydrofilní interakce; Binding Sites; Hydrophobic and Hydrophilic Interactions